Culture Technique and Management Practice of Empurau - Mohammad Bodrul, Munir; Roslianah, Asdari; Sharifah Lia Farliana, Wan Alias (UNIMAS CALM, 2021)
The course "Culture Technique and Management Practice of Empurau" is a virtual aquaculture training course. Students will be benefited to learn about the biology of empurau fish, its culture technique and management practice particularly farm management along with it's potential importance. This online course has been prepared with the UNIMAS FSTS research collaborator "Puri Johan Aquaculture Sdn Bhd."- a royal practitioner for empurau (Tor tambroides) fish. This industry shared their practical experiences on farm management of Empurau fish aquaculture. Overall, it is expected that students will be achieved basic comprehensive knowledge on Empurau or Tor tambroides culture technique and management practice in virtual.